Barium Staminate as Semiconductor Working Electrodes for Dye-Sensitized Solar Cells - Fu-an Guo; Guoqiang Li; Weifeng Zhang (International Journal of Photoenergy)
Dye-sensitized solar cells (DSSCs) are fabricated with perovskite-type BaSnO3 as the photoelectrode materials. Different preparation methods including coprecipitation, hydrothermal, and solid state reaction are employed to synthesize BaSnO3 particles to optimize the photoelectric activities of electrode materials. The photoelectric properties of BaSnO3 particles and the performances of DSSCs are investigated by surface photovoltage spectroscopy and current-voltage measurements. The light-to-electricity conversion of 1.1% is preliminarily reached on the DSSC made of the coprecipitation-derived BaSnO3 particles. Large current density of hole injection into the HOMO level of N719 dye from the valence band of BaSnO3 and reduced photogenerated charge recombination in BaSnO3 could be responsible for the observed solar cell performance of the DSSC fabricated from the coprecipitation-derived BaSnO3 particles.